Knowledge of Parents about Covid with Anxiety Levels in Taking their Children to Pediatric Dentists during Covid-19 Pandemic (A Cross-Sectional Survey) - Rizma Khumayanti; Imam Sarwo Edi; Silvia Prasetyowati; Wannarat Lawang; Isnanto Isnanto (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Knowledge is the result of human sensing, or the result of someone knowing about objects through the senses they have, namely the senses of sight, smell, hearing, taste, and touch. Covid-19 is a disease caused by SARS-CoV-2 which infects the respiratory system. The spread of Covid-19 has the potential to trigger anxiety disorders in the community. The problem in this study is that data on the visitation of pediatric patients at the FDS Prapen dental clinic showed a decrease in the number of visits during the Covid-19 pandemic. The purpose of this study was to determine the relationship between parental knowledge about Covid-19 and the level of anxiety in taking their child to a pediatric dentist during the Covid-19 pandemic. This research method was a cross-sectional analytic research study design. The samples in this study were the parents of patients who took their children to the FDS Prapen clinic during the Covid-19 pandemic, with the amount of 40 respondents and the sample calculation used accidental sampling technique. The data collection method used was a questionnaire. Data analysis technique used the Rank Kendall's Tau test. The results showed that the knowledge of respondents about Covid was in (85%) good category and (92,5%) respondents did not experience anxiety when taking their children to a pediatric dentist during the Covid-19 pandemic. Analysed data showed (p=0,361), it means p values > 0,05 it be conclude that there is no relationship between the level of knowledge about Covid with anxiety Level in Taking care the children dentist during Covid-19 pandemic. This research can be additional information for clinic dentistry especially in the management of patient care during the Covid-19 pandemic and for parents of patients who experience anxiety.